Favourable Steel Structures using High Strength Steels. Issue 2 (1st September 2021) - Gong, Fengyan; Dürr, André; Bartenbach, Jochen
Abstract: As a part of the European RFCS‐project STROBE, HOCHTIEF Engineering has developed a calculation programme as the basis of a web‐tool for the design and optimization of steel beams. The programme is suitable for steel girders of normal strength and for high strength girders up to S690 including welded hybrid girders. In this paper, the developed calculation programme as well as several case studies will be presented based on an existing project which compares the design of floor systems of conventional strength steel S355 with high strength steel floor systems. The benefits of solutions using modern high strength steels for sustainable construction relative to conventional strength steel S355 in terms of saving weight and costs will be highlighted.